Constituents of Acacia nilotica (L.) Delile with Novel Kinase Inhibitory Activity - Ahmadu, Augustine A.; Agunu, Abdulkarim; Nguyen, Thi-Ngoc-Dung; Baratte, Blandine; Foll-Josselin, Béatrice; Ruchaud, Sandrine; Serive, Benoît; Bach, Stéphane (Planta Medica International Open, 2017)
Acacia nilotica (L.) Delile belongs to the genus Acacia, which includes about 1400 species in subtropical and tropical Africa including Nigeria, Senegal, Egypt, and Mozambique as well as Asia from India to Burma. This plant is traditionally used to treat several pathologies such as mouth, ear, and bone cancer. Moreover, it possesses many other biological activities (antidiarrheal, anti-inflammatory, antimicrobial, and antifungal). We report here the extraction, purification, and identification of two known compounds [ethylgallate and (+)-catechin] from the bark of the tree that were further tested for their inhibitory activities against a panel of disease-related protein kinases. Both compounds were active, and (+)-catechin showed the best activity by inhibiting nine out of fourteen protein kinases with an IC50 value in the µg/mL range. This compound gave the highest activity against CLK1 with an IC50 of 2.1 µg/mL. The ethyl acetate extract and its components, such as catechins and other polyphenols, which also had protein kinase inhibitory activity, can be exploited in the research for anticancer agents.
Keywords: Acacia nilotica; Leguminosae; (+)-catechin; ethyl gallate; protein kinases